Isolation of lactic acid bacteria strain Staphylococcus piscifermentans from Malaysian traditional fermented shrimp cincaluk - Tengku Abdul Hamid, Tengku Haziyamin; Azhari, Siti Hajar (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
Lactic acid bacteria is well known for it uses as starter culture in various fermented food, and it functions as a good natural antimicrobial agent. Cincaluk, a Malaysian fermented shrimp product commonly found in traditional dishes is commonly enriched with LAB. Out of 50 colonies from a local cincaluk, 7 strains were successfully isolated and shown to be positive in lactose utilization and catalase tests. The majority of the isolates from cincaluk showed Gram-positive cocci morphology and belonged to the group Staphyloccoccus spp. By using agar disc diffusion method, the anti-bacterial properties of these isolates (namely isolate 1, 2, 3, 4, 5, 6, and 7) moderately inhibited the growth of several pathogenic strains, i.e., Escherichia coli, Staphylococcus aureus, Salmonella typhimurium and Bacillus subtilis which were used as indicator bacteria. Other than isolates 1, 2, 3 and 5; the 16S rRNA gene for isolate 6 and 7 were successfully amplified. The 16S rRNA gene fragment from isolate 7 was successfully cloned and sequenced. Based on rRNA sequences, both isolates 6 and 7 belonged to the group Staphylococcus piscifermentans, a rare strain previously reported to be specifically isolated exclusive from fish sources.